Yoga Therapy for Pregnant Women to Overcome Stress in Premature Labor - Ariani, Novida (PT. Anagata Sembagi Education, 2025)
Globally, prematurity is one of the leading causes of death in children under the age of 5. Premature childbirth is a problem in the world, including Indonesia. The occurrence of preterm labor in general is due to the influence of stress that results in HPA activation in the mother and fetus. The provision of complementary therapy to pregnant women is one of the alternatives that health workers can provide to pregnant women to prevent premature labor. This article wants to raise how the effect of giving yoga therapy to pregnant women to overcome stress in premature labor. Data were collected using electronic databases through Google Schoolar, Pubmed and Science Direct related to the original article that researched the provision of yoga therapy to overcome stress in premature labor that met the inclusion and exclusion requirements. Based on the total library, 600 were identified and as many as 100 additional articles were identified. A total of 630 studies failed to meet the inclusion criteria and 70 articles were read in their entirety, so that as many as 11 publications were used as references. There is an effect between the administration of yoga on the incidence of premature labor.